1976
DOI: 10.1002/bip.1976.360150310
|View full text |Cite
|
Sign up to set email alerts
|

Proton and phosphorus nmr studies of d‐CpG(pCpG)n duplexes in solution. Helix–coil transition and complex formation with actinomycin‐D

Abstract: SynopsisThe Watson-Crick imino and amino exchangeable protons, the nonexchangeable base and sugar protons, and the backbone phosphates for d-CpG(pCpG),, n = 1 and 2, have been monitored by high-resolution nmr spectroscopy in aqueous solution over the temperature range Oo-90°C. The temperature dependence of the chemical shifts of the tetramer and hexamer resonances is consistent with the formation of stable duplexes a t low temperature in solution. Comparison of the spectral characteristics of the tetranucleoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
63
2

Year Published

1976
1976
1986
1986

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 139 publications
(75 citation statements)
references
References 44 publications
10
63
2
Order By: Relevance
“…These values are indicative of the presence of one platinum atom/ oligonucleotide molecule, assuming a slight decrease of the cmax value upon binding of cisPt [lo, 141. At the reaction temperature used a large proportion of the selfcomplementary oligodeoxynucleotides are in the doublestranded form [20,211. Therefore, the above-mentioned observations show that cisPt has a strong preference for intrastrand cross-linking.…”
Section: Generalmentioning
confidence: 99%
“…These values are indicative of the presence of one platinum atom/ oligonucleotide molecule, assuming a slight decrease of the cmax value upon binding of cisPt [lo, 141. At the reaction temperature used a large proportion of the selfcomplementary oligodeoxynucleotides are in the doublestranded form [20,211. Therefore, the above-mentioned observations show that cisPt has a strong preference for intrastrand cross-linking.…”
Section: Generalmentioning
confidence: 99%
“…servable when the double helix was predominantly intact but broadened with increasing coil concentration. An alternate NMR approach monitors the entire helix-coil transition as followed by the nonexchangeable protons and the, phosphates in D20 solution (11)(12)(13)(15)(16)(17).Nuclear magnetic resonance spectral line widths yield kinetic information about the helix-coil transition when the exchange rate is on the order of the chemical shift difference between the helix and coil states. It will be demonstrated that the adenine H2 proton in poly(dA-dT) exhibits an about 1 ppm chemical shift difference between the two states and provides a handle for monitoring the kinetic aspects of the helix-coil transition.…”
mentioning
confidence: 99%
“…The servable when the double helix was predominantly intact but broadened with increasing coil concentration. An alternate NMR approach monitors the entire helix-coil transition as followed by the nonexchangeable protons and the, phosphates in D20 solution (11)(12)(13)(15)(16)(17).…”
mentioning
confidence: 99%
“…The steroid diamine is nonplanar and therefore unable to insert into such a site while spanning the backbone phosphates through its charged ends. It therefore appears that the steroid diamine must partially insert into a binding site generated by unstacked (21), and complexation shifts of t2 ppm are observed for actinomycin D-nucleic acid interactions (22). The (Figs.…”
Section: Resultsmentioning
confidence: 99%